Personal Effects : Essays on Memoir, Teaching, and Culture in the Work of Louise DeSalvo - Giunta, Edvige; Caronia, Nancy (Book collections on Project MUSE., 2015)
"The two editors and eighteen scholars and creative nonfiction writers offer a lucid view of a writer who has produced one of the most provocative bodies of memoir writing in contemporary US literature, a scholar who has enriched our understanding of Virginia Woolf, and a teacher who has transformed countless lives"--